Investigation of chemical transformations in the hydrocarbon composition of the working fluid "hidronikoyl» fh-51 - Соловйов, А.М.; Кузнєцова, О.Я.; Нетреба, Ж.М.; Вихрестюк, М.І. (Proceedings of National Aviation University, 2007)
The results of structurally-group composition research of standards of commodity and after 3600 hours flight of aviation hydraulic liquid of «Гидроникойл» FH-51 are presented. Given liquid was investigated by the methods of distillation and liquid chromatography. Obtained results demonstrate that after thermal-oxidative degradation of carbohydrates it composition changes. And as a result the quality and running ability of considered working liquid decrease. Today airline enterprises quality control system does not check such chemical transformations in hydraulic liquids composition. Thus, it is confirmed, that present quality control system of hydraulic liquids is not scientifically valid and it does not provide modern high demands to saving of a working liquid quality at it exploitation in airplane hydraulic system .Therefore the task of improvement of the existent quality control system of hydraulic liquids is actual.